Changing Nature of Conflicts, Violence and Environmental Crisis: Exploring the Impact of Global Crises on Societies and Future Generations (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Every day, we are confronted on ourtelevisions and in the newspapers by a relentless tide of tragic events andcrises, by violence terrorist attacks and conflicts in all regions of theworld. There is, in consequence, an intense and deep public concern about thestate of our world, about relations between peoples and ethnic and religiousgroups and about the prospects for a stable, peaceful world for futuregenerations. Viewed from the perspective of the rich, developed countries, amajor change has occurred.